The Cause-and-Effect Linkage Between Quality Management and Balanced Scorecard (Malaysian Management Journal, 2008)
The objective of this study was to scientifically examine the path relationship between Quality Management (QM) and cause-and-effect performance linkage. According to QM literature, many studies have been carried out to investigate the relationship between QM and organisational performance (OP). Nevertheless, the report of these studies seems to ignore the cause-and-effect linkage of OP dimension as discussed in the Balanced Scorecard literature. The findings of this study provided evidence to support the concept of cause and effect linkage of performance dimension.